THE EFFECT OF VOLUNTARY DISCLOSURE PROGRAM ON TAX RECEIPTS AT THE KABANJAHE PRIMARY TAX SERVICE OFFICE - Gembira Marbun; Rita Rhubysta Br Surbakti (PT. Radja Intercontinental Publishing, 2024)
This study aims to determine the effect of the voluntary disclosure program on tax revenue at the Kabanjahe Pratama Tax Service Office. The data collection technique in this study uses a questionnaire in the form of a Likert scale. Respondents in this study are taxpayers registered at the Kabanjahe Pratama Tax Service Office. The number of taxpayers who are samples in this study is 100 respondents. The research method used in this study is purposive sampling. The analysis technique used in this study is a simple linear analysis technique. The results of the study indicate that the voluntary disclosure program has a positive and significant effect on tax revenue. This means that if the voluntary disclosure program increases, tax revenue will also increase. The conclusion in this study is that the higher the taxpayers who participate in the Voluntary Disclosure Program, the higher the tax revenue. The researcher's suggestion is that the government should further improve the Voluntary Disclosure program in order to increase tax revenues, which will increase state revenues.